Effect of Pregnant Mothers’ Forum Participation on Birth Preparedness and Complication Readiness among Pregnant Women in Dale District, Southern Ethiopia: A Comparative Cross-Sectional Study - Bizuayehu Bogale; Ayalew Astatkie; Negash Wakgari (Journal of Pregnancy)
Background. Pregnant mothers’ forum is the innovative intervention strategy being implemented in Ethiopia to facilitate birth preparedness and complication readiness practice. However, its effect on birth preparedness and complication readiness has not been investigated. Objective. This study assessed the association of participation in pregnant mothers’ forum with birth preparedness and complication readiness plan among pregnant women in Dale District. Methods. A community-based comparative cross-sectional study was conducted among 604 pregnant women (302 who were forum members [exposed] and 302 who were forum nonmembers [unexposed]). Multistage sampling technique was used to select respondents. Data were collected door to door using a pretested and structured questionnaire through face-to-face interview. Data were entered and analyzed using SPSS version-20. Multiple logistic regression analysis was used to identify the effect of pregnant mothers’ forum membership on birth preparedness and complication readiness adjusting for other variables. Results. About 22.5% of pregnant women were well prepared for birth. A quarter (25.8%) of the women was prepared for the anticipated complications of whom 20.7% were the forum members. Being pregnant mother’s forum member (AOR=2.86, 95% CI=1.50,5.44), having focused counseling (AOR=3.73, 95% CI=1.17,11.83), monthly income (AOR=2.55, 95% CI=1.44,4.51), having antenatal care (AOR=3.73,95% CI=1.05,13.21), and institutional delivery during last birth (AOR=2.41, 95% CI=1.38,4.22) were significantly associated with birth preparedness. Similarly, being forum members (AOR=3.55, 95%CI=2.18, 5.78) and having antenatal care attendance before or at four months of gestational age (AOR=3.16, 95%CI=2.04, 4.91) were found to be predictors of complication readiness. Conclusion. In this study, birth preparedness and complication readiness is found to be low. However, it was significantly higher among forum members compared to forum nonmembers. Hence, efforts should be targeted to strengthen the pregnant mothers’ forum and enroll the pregnant women to antenatal care service at early stage of the pregnancy.